Custo adaptativo da indução de resistência por Saccharomyces boulardii em feijoeiro (Phaseolus vulgaris L.) - Müller, Sidnei Francisco (2011)
The use of chemicals as a means of controlling bean diseases is an established practice for the crop. Despite the satisfactory results for most diseases, it is a form of control that can result in serious risk to the environment and human health. Thus, alternative pest control practices have received a great importance, mainly because of its direct applicability for small producers. The alternative control includes biological control and resistance induction, which differs from the first not to act on a specific microorganism, but for providing the plant treated to activate its latent defenses to be prepared when a pathogen trying to infect it. Molecules of biotic and abiotic origin capable of inducing resistance in plants are called elicitors. Among the biotic origin the extracts of yeasts such as Saccharomyces cerevisiae, has been used to induce resistance to control various pathogens from different cultures. S. cerevisiae has been successfully employed, but constantly seeks other organisms capable of use in alternative control. Thus, the yeast Saccharomyces boulardii has been researched to its use in biological control of plant pathogens. In three field assays in dry seasons of 2009 and 2010, and rain season used in 2009, using the bean group Rosinha, was evaluated the effectiveness of the yeast S. boularddi as inducer of resistance and the methabolic cost embedded in it. Foliar applications were carried out with yeast in commercial form, with the mass of cells obtained from the filtering medium YEPG with this yeast and with the filtrate of the medium. The yield, weight of 100 grains, grain number per plant and pods were evaluated. It was noted the low incidence of pathogens in the assays, precluding their measurement by diagrammatic scale. Because the balanced environment, there may have been the biological control of pathogens, the theory of trophobiosis, or even the induction of natural resistance both by microorganisms acting in plants, by rhizobacteria and by the use of biofertilizers leaf. There were no significant differences in parameters, indicating a possible absence of metabolic cost for the application of yeast. This possible fitness cost may have been obscured by the nutritional balance of plants, as well as possible induction in all treatments by local conditions of cultivation and management used. Under agricultural and environmentally balanced nutrition, foliar applications of yeast S. boulardii did not result in apparent metabolic cost